Age-specific seroprevalence of serogroup C meningococcal serum bactericidal antibody activity and serogroup A, C, W135 and Y-specific IgG concentrations in the Turkish population during 2005 - Ceyhan, Mehmet; Yildirim, Inci; Balmer, Paul; Riley, Christine; Laher, Gouri; Andrews, Nick; Schultze, Viola (Elsevier Sci Ltd, 2007)
Like many other developing countries; there is no accurate information about the antibody levels against Neisseria meningitidis in Turkey. We collected serum samples from four health centers located in different geographic regions and stratified according to age in order to obtain a baseline seroprevalence of protective antibodies to meningococcal serogroup C and provide data on seroprevalence of IgG antibodies to serogroups A, C, W135 and Y. Sera were tested for serum bactericidal antibodies (SBA) to serogroup C meningococci using rabbit serum as the complement source and by a bead based assay for serogroup A, C, W135 and Y-specific IgG. It was observed that 30% and 12% of individuals within the study population had SBA titers of >= 8 and >= 128, respectively. Overall; at least 70% of the population are susceptible (SBA titer < 8) to meningococcal serogroup C disease. The rate of susceptibility was highest in infants aged 7-12 months and young children (1-4 years). Regardless of age, for serogroup A, C, W135 and Y, 60.5%, 27.2%, 12.3% and 19.2% of subjects, respectively, had serogroup-specific IgG concentrations >= 2 mu g/mL. These data highlight that a large proportion of the Turkish population are susceptible to serogroups C, W135 and Y and should be considered, along with serogroup-specific disease incidence data, in future decisions on possible meningococcal vaccination programmes. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: meningococcal; serum bactericidal antibody; seroprevalence